A mediastinal malignant thyroid paraganglioma: A case report and literature review. (January 2022) - Yankov, Georgi; Ivanovа, Silvia; Genadieva, Marusya; Alexieva, Magdalena; Yanev, Nikolay; Ivanova, Desislava
Abstract: Introduction and importance: Thyroid cancer is the most common endocrine malignancy, while primary paraganglioma of the thyroid gland (TP) is an unusual tumour and in rare cases, this disease tends to mimic thyroid cancer. They are rare extra-adrenal neuroendocrine tumours originating from the neural crest, and are found almost exclusively in the head and neck area. Case presentation: We present a case of a 53-year-old man, in whom a mediastinal lesion originating from the left lobe of the thyroid gland was found on routine ultrasound and subsequent computed tomography (CT). Clinical discussion: Total thyroidectomy and lymph dissection were performed. A review of the literature was made and a discussion was held regarding the diagnosis, the importance of surgical treatment and further behaviour. Conclusion: Surgical removal of the thyroid gland is the main treatment, followed by radiation therapy. The diagnosis and differential diagnosis with other thyroid tumours is extremely important in terms of subsequent behaviour and prognosis. Highlights: Lesions like the one we described should be operated on. Examination of surgical specimen is more accurate than transcutaneous biopsy. Cervicotomy is an appropriate approach but extension to sternotomy could occur.